1976
DOI: 10.1002/oms.1210110514
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ionization mass spectrum of peroxyacetylnitrate

Abstract: The chemical ionization mass spectrum of peroxyacetylnitrate, a major component of photochemical smog highly toxic to man and plants, was obtained using both methane and isobutane as reagent gas. The spectrum contains a [M + HI+ ion at m/e 122, intense fragment ions at m/e 43 [CH,CO]+ and m/e 46 [NO,]+, and less intense ions at m/e 61 [CH,ONO]+, m/e 77 [CH30NOz]+ and m/e 88 [+O=CCH,ONO] formed by internal rearrangements. These results confirm the commonly accepted structure for peroxyacetylnitrate, CH,(CO)OONO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…decomposition to alkyl nitrate, alkaline decomposition to carboxylic acid, and identification of the carbonyl product(s) of the gas-phase decomposition in the presence of NO, are compound-specific. These tests represent a simple, cost-effective alternative to structure elucidation using conventional methods such as infrared spectroscopy and mass spectrometry, which are suitable for the identification of peroxyacyl nitrates as a group but have limited applicability to structure confirmation for individual compounds (1,14,32,33).…”
Section: Resultsmentioning
confidence: 99%
“…decomposition to alkyl nitrate, alkaline decomposition to carboxylic acid, and identification of the carbonyl product(s) of the gas-phase decomposition in the presence of NO, are compound-specific. These tests represent a simple, cost-effective alternative to structure elucidation using conventional methods such as infrared spectroscopy and mass spectrometry, which are suitable for the identification of peroxyacyl nitrates as a group but have limited applicability to structure confirmation for individual compounds (1,14,32,33).…”
Section: Resultsmentioning
confidence: 99%
“…Spicer et al [1998] and Srinivasan et al [1998] reported ambient air measurements and laboratory investigation of P AN using negative ion chemical ionization mass spectrometry, respectively. Measurements of PAN by mass spectrometry using other ionization methods (i.e., electron impact ionization [e.g., Bertman andRoberts, 1991], photoionization [Kacmarek et al, 1978], and positive ion chemical ionization [Pate et al, 1976]) have been reported previously; however, these techniques have been used in laboratory experiments to investigate the structure and chemical properties of PANs but have not been used forambient air measurements, probably because of in-sufficientsensitivity. Somestudies using GC/NiCI MShave reported trace gas measurements other than PAN in ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…61 The chemical ionization mass spectrum of PAN was obtained in 1976. 62 Being an energetic molecule, the parent peak of PAN was not observed in the positive ion mass spectrum. However, since PAN has a high ECD cross section, the negative ion mass spectrum of PAN can be detected with high sensitivity.…”
Section: Propertiesmentioning
confidence: 95%
“…The mass spectrum of PAN was first determined using electron impact ionization in 1969 as part of a study showing the release of singlet molecular oxygen (O 2 1 Δ g ) occurring during the base decomposition of PAN . The chemical ionization mass spectrum of PAN was obtained in 1976 . Being an energetic molecule, the parent peak of PAN was not observed in the positive ion mass spectrum.…”
Section: Measurement Methodsmentioning
confidence: 99%